A Randomized Trial of Prenatal n-3 Fatty Acid Supplementation and Preterm Delivery. Issue 1 (March 2020) - Makrides, M.; Best, K.; Yelland, L.; McPhee, A.; Zhou, S.; Quinlivan, J.; Dodd, J.; Atkinson, E.; Safa, H.; van Dam, J.; Khot, N.; Dekker, G.; et al.
Abstract : ( N Engl J Med . 2019;381(11):1035–1045) Although early preterm deliveries (before 34 wk of gestation) only comprise 20% of all preterm deliveries, they are more likely to result in neonatal death or childhood disability. The rate of preterm deliveries is rising around the world, and previous research has indicated a significant relationship between reduced fish consumption during pregnancy and higher preterm delivery rates. In this study, the investigators examined the connection between n-3 long-chain polyunsaturated fatty acid (PUFA) supplements and the percentage of pregnant women who experienced preterm delivery.